A process-scheduling simulator based on virtual reality technology - De Paiva Guimaraes, Marcelo (2016)
A process-scheduling algorithm is a fundamental operating system function that manages the assignment of CPU (Central Processing Unit) processes. It aims to make the system efficient, fast, and fair, allowing as many processes as possible to make the best use of the CPU at any given time. Understanding scheduling algorithms and their impact in practice is a challenging and time-consuming task for students, given the differing features of each operating system. Operating system simulators are usually based on either a command line or bidimensional front-end interface. This paper presents a process-scheduling simulator based on virtual reality technology that allows students to develop their empirical skills while learning process-scheduling algorithms. The simulator allows the learner to navigate inside a computer motherboard and interact with its components in multi-projection environments such as CAVE-like systems (Cave Automatic Virtual Environment), on a desktop, in a Web browser, or using an HMD (head-mounted display) such as Google Cardboard.